Faktor – faktor Rasio Keuangan meliputi: Rasio Likuiditas, Rasio Solvabilitas, Rasio Profitabilitas, Rasio Aktivitas, dan Rasio Investasi, Berpengaruh Terhadap Kinerja Laporan Keuangan (Literature Review Manajemen Keuangan) - Gisca Dwi Desriyunia; Kartika Wulandhari; Della Puspita; Jasmine Jasmine; Tri Yulaeli (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This Literature Review article identifies the biggest factors that influence the performance of a company's financial statements, which can help the company make the right administrative decisions related to the management of financial ratios and the company's financial performance. This Literature Review article discusses the benefits of providing Financial Ratios including; Liquidity Ratios, Solvability Ratios, Activity Ratios, Profitability Ratios, and Investment Ratios to the Company's Financial Statement Performance, an introductory literature study on Financial Management. Writing this article aims to build a hypothesis of the influence between variables to be used in further research. From the research results it was found that: (1) Financial Ratios with Financial Performance Companies have a close relationship in building company efficiency. (2) Effect of Financial Ratios on Company Financial Performance (3) Relationship between Financial Ratios and Company Financial Performance in the aspect of company value growth.